The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2318-0331.011716110
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of land use scenarios in the Camboriú River Basin using the SWAT model

Abstract: Changes in the Earth's landscape have been the focus of much environmental research. In this context, hydrological models stand out as tools for several assessments. This study aimed to use the Soil and Water Assessment Tool (SWAT) hydrological model to simulate the impact of changes in land use in the Camboriú River Watershed in the years 1957, 1978, and 2012. The results indicated that the SWAT model was efficient in simulating water flow and sediment transport processes. Thus, it was possible to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
11
0
5
Order By: Relevance
“…This module uses a hydrological transport model, which is based on, inter alia, meteorological data, the quantity of surface runoff and the amount of soil fertilization, and enables us to carry out the analysis of phenomena and processes connected with the transportation of nitrogen loads in a sub-basin. With the use of the Macromodel DNS/SWAT, all the elements form a homogenous, numerical sub-basin model that enables us to analyse different scenarios of sub-basin exploitation in different meteorological and hydrological conditions [25,26]. The SWAT module has been used many times to create scenarios of land use change [27,28,29]; in most cases these scenarios were used to predict future events and their impact on the water quality of a catchment.…”
Section: Dns/swat Macromodelmentioning
confidence: 99%
“…This module uses a hydrological transport model, which is based on, inter alia, meteorological data, the quantity of surface runoff and the amount of soil fertilization, and enables us to carry out the analysis of phenomena and processes connected with the transportation of nitrogen loads in a sub-basin. With the use of the Macromodel DNS/SWAT, all the elements form a homogenous, numerical sub-basin model that enables us to analyse different scenarios of sub-basin exploitation in different meteorological and hydrological conditions [25,26]. The SWAT module has been used many times to create scenarios of land use change [27,28,29]; in most cases these scenarios were used to predict future events and their impact on the water quality of a catchment.…”
Section: Dns/swat Macromodelmentioning
confidence: 99%
“…From this perspective, some authors (Deng et al, 2015;Fan & Shibata, 2015;Neupane & Kumar, 2015;Sajikumar & Remya, 2015;Blainski et al, 2017;Gashaw et al, 2018;Zhang et al, 2018;Pereira et al, 2016;Silva et al, 2018) highlight that the land use and cover changes, mainly due to anthropic actions, on a basin have an effect on variables inherent to the water balance, such as the soil infiltration rate, the evapotranspiration, surface runoff and the water bodies recharge. Putting them all together, it's of major importance for the management of water resources to comprehend the impacts of the change of land use and cover on the basin runoff characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The authors had satisfactory results and concluded that the model may be used with good estimations of the region's water balance. Blainski et al (2017) applied the SWAT model seeking to evaluate the flow alterations due to the changes on land use and cover observed from 1957 until 2012, in Camboriú basin in the Santa Catarina State, southern region of Brazil. They noticed, from the daily flow permanence curve, that the flowing between Q 60 (flow overcome in 60% of the time) and the Q 90 (flow overcome in 90% of the time and which represents the drought condition) was lower in the land use and cover 2012's scenario in comparison to the 1957's one.…”
Section: Introductionmentioning
confidence: 99%
“…O método a ser escolhido depende de vários fatores: escala da bacia, tempo de deslocamento da onda da cheia, recursos disponíveis e dos resultados necessários. Então, para realizar a previsão de vazão, podem ser utilizadas metodologias baseadas em: propagação de ondas de cheias, transformação de chuva em vazão e transformação de chuva em vazão com informação adicional de previsão quantitativa de precipitação (Fan, 2015) As modificações dos recursos naturais, causada pela ação antrópica, influenciam nos processos hidrológicos, podendo resultar em eventos extremos, como inundações, estiagens, produção e transporte de sedimentos, entre outros (Blainski et al, 2017;Passos, 2017;Siqueira, 2017;Magalhães e Vieira, 2018). Juntamente com isto, surgiu nas últimas décadas a preocupação com problemas que se manifestam em de grande escala, como as mudanças climáticas e as alterações do uso do solo, o que motivou o desenvolvimento dos estudos voltados para hidrologia de grandes bacias.…”
Section: Introductionunclassified